2018
DOI: 10.29086/2519-5476/2018/sp21a7
|View full text |Cite
|
Sign up to set email alerts
|

Geography Student Teachers’Perceptions of Online Problem-based Learning Activities: A Case Study

Abstract: As online learning is being embraced in higher education, geography modules that implement problem-based learning can integrate online platforms to support geography curriculum delivery and facilitate student collaboration. The aim of this case study was to explore full-time BEd geography student teachers' (n = 98) perceptions of online problem-based learning activities in two third-year geography modules. The study used quantitative and qualitative research approaches based on questionnaire applications. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 32 publications
(38 reference statements)
0
10
0
Order By: Relevance
“…Regular communication and collaboration with students do promote a teaching presence and can lead to higher-order thinking (Gani 2018). In addition, scaffolding is also an important strategy that can be used by online tutors to support in solving problems (Golightly & Van der Westhuizen 2018). Although online tutors, who are not the lecturers, are often used in BL environments, Pool et al (2017) reported in their study that students preferred the presence of the lecturer.…”
Section: Teaching Presencementioning
confidence: 99%
See 4 more Smart Citations
“…Regular communication and collaboration with students do promote a teaching presence and can lead to higher-order thinking (Gani 2018). In addition, scaffolding is also an important strategy that can be used by online tutors to support in solving problems (Golightly & Van der Westhuizen 2018). Although online tutors, who are not the lecturers, are often used in BL environments, Pool et al (2017) reported in their study that students preferred the presence of the lecturer.…”
Section: Teaching Presencementioning
confidence: 99%
“…• CL Cruywagen 2015;Gambiza 2009) • PBL (Gambiza 2009;Golightly & Van der Westhuizen 2018;Massyn 2009) • flipped classroom (Le Roux & Nagel 2018). used the combined BL model to design a CL-BL environment.…”
Section: Approaches and Activities Used In Blended Learningmentioning
confidence: 99%
See 3 more Smart Citations